Reproductive cycle and ovarian development of the marine ornamental shrimp Stenopus hispidus in captivity - Gregati, Rafael A. [UNESP]; Fransozo, Vivian [UNESP]; Lopez-Greco, Laura S.; Lucia Negreiros-Fransozo, Maria [UNESP] (Elsevier B.V., 2010)
The reproductive cycle and ovarian development of the marine ornamental shrimp Stenopus hispidus were described starting from adult mating pairs under laboratorial conditions. The pairs were individually kept in aquaria under constant conditions of salinity (35%.), temperature (26 +/- 0.5 degrees C) and photoperiod (12L:12D). Molting, mating, spawning and hatching were recorded during three consecutive reproductive cycles. Females at different stages of ovarian development were anesthetized and their ovaries were removed, photographed, fixed and processed for histological examination. Mating occurred after female molting. Mean incubation time was 22.8 +/- 2.1 days and mean intermolt periods were 25.5 +/- 2.3 days for females and 26 +/- 4.1 days for males. The ovaries varied in size and color during each reproductive cycle, which could be clearly seen through the transparent carapace. Spent ovary (translucent), lasted for 3 days after egg spawning; developing ovary (white), lasted 7 days; developed ovary (light green), between 5 and 8 days and advanced ovary (dark green) lasts 10 to 13 days. Microscopically, the ovarian stages differed in proportion of follicular cells, oocytes and oogonia. Follicular cells were abundant and mature oocytes were absent at the spent stage, while the number and size of secondary oocytes increased gradually thereafter. The present study indicates that S. hispidus can undergo multiple reproductive cycles under culture conditions. The changes in the macroscopic appearance of the ovary are strongly associated with the reproductive cycle. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Stenopus hispidus; Stenopodidea; Reproductive cycle; Gonad development; Ornamental shrimp